2018
DOI: 10.1097/iop.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomical Location of Hyaluronic Acid Gel Following Injection of the Upper Lip Vermillion Border: Comparison of Needle and Microcannula Injection Technique

Abstract: Most HA filler injected into the vermillion border after either microcannula or needle injection resides within the orbicularis oris muscle rather than in a subcutaneous/submucosal location. Injection with a microcannula shows a trend for more uniform intramuscular location compared with needle injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
9
0
4
Order By: Relevance
“…Cadaveric dissections that have carried out as preliminary proof of concept (data not shown), revealed the fatty area at the level of the lip was hardly present which in accordance with Blandford et al that reported HA gel filler augmentation of the vermillion border may result in filler location within the muscle and this injection plane seems safe regarding the location of the superior labial artery. 21 In a recent study performed on 41 healthy volunteers, Cotofana et al pointed out the most frequent location of labial arteries was the submucosal followed by intramuscular planes (58.5% and 36.2%, respectively). 13 Since Stylage M has a high elastic modulus (G′), it is suitable for deep implantation and a volumizing effect.…”
Section: Discussionmentioning
confidence: 94%
“…Cadaveric dissections that have carried out as preliminary proof of concept (data not shown), revealed the fatty area at the level of the lip was hardly present which in accordance with Blandford et al that reported HA gel filler augmentation of the vermillion border may result in filler location within the muscle and this injection plane seems safe regarding the location of the superior labial artery. 21 In a recent study performed on 41 healthy volunteers, Cotofana et al pointed out the most frequent location of labial arteries was the submucosal followed by intramuscular planes (58.5% and 36.2%, respectively). 13 Since Stylage M has a high elastic modulus (G′), it is suitable for deep implantation and a volumizing effect.…”
Section: Discussionmentioning
confidence: 94%
“…Blandford et al compared the injection of hyaluronic acid into the upper lip vermilion border to needle and microcannula injection techniques. They indicated that using a microcannula provides a more uniform administration of hyaluronic acid to the intramuscular zone (13).…”
Section: Discussionmentioning
confidence: 99%
“…19 Another cadaveric study of upper lip augmentation with HA filler demonstrated that most filler injected into the vermillion border after resides within the orbicularis oris muscle rather than in subcutaneous tissue or submucosa. 20…”
Section: Imaging and Histologic Studies Of Hyaluronic Acid Fillers mentioning
confidence: 99%